Cardiovascular risk factor profile in subjects with familial predisposition to myocardial infarction in Denmark. Issue 3 (June 1997) - Hippe, M; Vestbo, J; Bjerg, A M; Borch-Johnsen, K; Appleyard, M; Hein, H O; Andersen, P K; Jensen, G; Sørensen, T I
Abstract : STUDY OBJECTIVES: To identify possible modifiable mediators of familial predisposition to myocardial infarction (MI) by assessing the risk factor profile in individuals without MI in relation to parental occurrence of MI. DESIGN AND METHODS: Cross sectional survey of the general population. The odds of an adverse cardiovascular risk factor profile in subjects reporting parental occurrence of MI versus subjects not reporting parental occurrence were estimated by logistic regression models. SETTING: The Copenhagen Centre for Prospective Population Studies, where subjects investigated in three Danish prospective population studies are integrated. PARTICIPANTS: Subjects were 9306 females and 11, 091 males aged 20-75 years with no history of MI. A total of 1370 subjects reported maternal MI and 2583 reported paternal MI. MAIN RESULTS: Increased systolic and diastolic blood pressure, increased cholesterol level, low ratio between high density lipoprotein (HDL) and total cholesterol (TC), and heavy smoking, were more frequent in subjects with parental occurrence of MI than in controls irrespective of sex and age of the subjects. Maternal MI was more predictive for increased cholesterol and decreased HDL/ TC ratio than paternal MI, and the risk of an increased cholesterol level was higher in subjects aged 20-39 years than in older subjects. No differences in body mass index, triglycerides, and physical inactivity were observed. CONCLUSIONS: Subjects free of previous MI who reported a parental occurrence of MI had an adverse cardiovascular risk factor profile regarding systolic and diastolic blood pressure, total cholesterol, the ratio between HDL and total cholesterol, and smoking. Thus, these modifiable risk factors may be mediators of the familial predisposition to MI.